The Right Treatment at the Right Time in the Right Place. Issue 3 (March 2015) - Mckee, Jessica L.; Roberts, Derek J.; van Wijngaarden-Stephens, Mary H.; Vis, Christine; Gao, He; Belton, Kathy L; Voaklander, Don; Ball, Chad G.; Bratu, Ioana; Ibbotson, Geoffrey C.; Martin, Kevin; Engels, Paul; et al.
<x xml:space="preserve">Abstract</x> Objective: To evaluate the implementation of an all-inclusive philosophy of trauma care in a large Canadian province. Background: Challenges to regionalized trauma care may occur where transport distances to level I trauma centers are substantial and few level I centers exist. In 2008, we modified our predominantly regionalized model to an all-inclusive one with the hopes of increasing the role of level III trauma centers. Methods: We conducted a population-based, before-and-after study of patient admission and transfer practices and outcomes associated with implementation of an all-inclusive provincial trauma system using multivariable Poisson and linear regression and Cox proportional hazard models. Results: In total, 21, 772 major trauma patients were included. Implementation of the all-inclusive model of trauma care was associated with a decline in transfers directly to level I trauma centers [risk ratio (RR) = 0.91; 95% confidence interval (CI): 0.88–0.94; P < 0.001] and an increase in transfers from level III to level I centers (RR = 1.10; 95% CI: 1.00–1.21; P = 0.04). These changes in trauma care occurred in conjunction with a 12% reduction in the hazard of mortality (hazard ratio = 0.88; 95% CI: 0.84–0.98; P = 0.003) and a decrease in mean trauma patient hospital length of stay by 1 day (95% CI: 1.02–1.11; P = 0.02) after adjustment for differences in case mix. Conclusions: In this study, introduction of an all-inclusive provincial trauma system was associated with an increased number of injured patients cared for in their local systems and improved trauma patient mortality and hospital length of stay.